Analisis Faktor Yang Mempengaruhi Penggunaan QRIS Dalam Transaksi Keuangan Aparatur Sipil Negara (ASN) - Muslihatul Habbah, Siti Mauludah; Maheri Laksono, Sonny Subroto; Akbar, Taufik (Otonomi, 2026)
This study aims to analyze the factors that influence the intention of Civil Servants (ASN) in using QRIS, as well as the implications of the variables studied on the decision to use this system. The conclusion of the study provides a comprehensive overview of the relationship between individual factors, social factors, and supporting conditions with Intention to Use QRIS. The results show that Perceived Usefulness (X1) and Perceived Ease of Use (X2) have a positive effect on the intention of Civil Servants to use QRIS, indicating that the benefits and ease of use of the system increase user interest. Facilitating Condition (X4), Perceived Cost (X6), Promotional Activities (X7), and Attitude (X8) also have a significant effect, indicating that resource support, cost perception, promotional activities, and positive attitudes encourage system use. Conversely, Social Influence (X3) and Perceived Risk (X5) have no effect, indicating that social pressure or perceived risk are not determinants of intention to use QRIS. Simultaneously, these eight variables are proven to have a significant effect on Intention to Use QRIS. This finding confirms that civil servants' intentions are influenced by a combination of factors such as benefits, convenience, support, costs, promotions, and attitudes, which can be the basis for recommendations for QRIS implementation strategies in government environments.